High IDO1 Expression Is Associated with Poor Outcome in Patients with Anal Cancer Treated with Definitive Chemoradiotherapy - Mitra, Devarati; Horick, Nora K.; Brackett, Diane G.; Mouw, Kent W.; Hornick, Jason L.; Ferrone, Soldano; Hong, Theodore S.; Mamon, Harvey; Clark, Jeffrey W.; Parikh, Aparna R.; Allen, Jill N.; Ryan, David P.; et al. (The oncologist (Dayton, Ohio), 2019)
Background This study characterizes the tumor‐immune microenvironment in pretreatment, localized anal squamous cell carcinoma (ASCC), including two markers that have not previously been studied in ASCC: indoleamine 2,3 dioxygenase 1 (IDO1) and human leukocyte antigen (HLA) class I. Materials and Methods Retrospective review identified 63 patients with ASCC receiving definitive chemoradiation between 2005 and 2016 with pretreatment tissue available. Immunohistochemistry was used to quantify cluster of differentiation 8 (CD8), programmed cell death protein 1, programmed death‐ligand 1, HLA class I, and IDO1. Cox proportional hazards models evaluated associations between outcomes and immune markers, controlling for clinical characteristics. Results With a median follow‐up of 35 months, 3‐year overall survival was 78%. The only marker found to have a robust association with outcome was tumor IDO1. In general, the percentage of tumor cells expressing IDO1 was low (median 1%, interquartile range 0%–20%); however, patients with >50% of tumor cells expressing IDO1 had significantly worse overall survival (hazard ratio [HR] 4.7, p = .007) as well as higher local recurrence (HR 8.6, p = .0005) and distant metastasis (HR 12.7, p = .0002). Tumors with >50% IDO1 were also more likely to have the lowest quartile of CD8 infiltrate (<40 per high‐power field, p = .024). Conclusion ASCC has a diverse immune milieu. Although patients generally do well with standard therapy, IDO1 may serve as a prognostic indicator of poor outcome and could help identify a patient population that might benefit from IDO‐targeted therapies. Implications for Practice After definitive chemoradiation, patients with locally advanced anal cancer may experience significant treatment morbidity and high risk of recurrence. The goal of the current study is to identify novel prognostic factors in the tumor‐immune microenvironment that predict for poor outcomes after definitive chemoradiation. This study characterizes the tumor‐immune microenvironment in pre‐treatment, localized anal squamous cell carcinoma (ASCC), including two markers which have not previously been studied in ASCC: indoleamine 2,3 dioxygenase 1 (IDO1) and HLA class I. With a median follow‐up of 3 years, this study demonstrated that high IDO1 expression is correlated with significantly worse 3‐year overall survival (88% vs. 25%). Whereas recent studies of IDO1 inhibitors have shown mixed results, this study suggests that patients with anal cancer with high IDO1 expression have dismal prognosis and may represent a patient population primed for response to targeted IDO1 inhibition. 摘要 背景。本研究描述了局部肛门鳞状细胞癌 (ASCC)治疗前的肿瘤免疫微环境，包括以前未在 ASCC 中研究的两种标志物:吲哚胺 2,3 双加氧酶 1 (IDO1) 和人白细胞抗原 (HLA) I 类的特性。 材料和方法。回顾性调查确定了在 2005 年至 2016 年期间接受根治性放化疗的 63 例 ASCC 患者，并可获取治疗前组织。免疫组织化学用于量化分化簇 8 (CD8)，程序性细胞死亡蛋白 1，程序性死亡‐配体 1，HLA I 类和 IDO1。Cox 比例风险模型，在控制临床特征的同时，评估预后和免疫标记物之间的关联。 结果。中位随访时间为 35 个月，3 年总生存率为 78%。发现与预后具有强烈关联的唯一标记物是肿瘤 IDO1。通常，表达 IDO1 的肿瘤细胞的百分比较低(中位数 1%，四分位数范围 0%‐20%)；然而，表达 IDO1 的肿瘤细胞 > 50% 的患者的总生存率 [风险比 (HR)4.7， p = 0.007]显著降低，并且局部复发率(HR 8.6， p = 0.000 5)和远处转移发生率(HR 12.7, p = 0.000 2)较高。具有 > 50% IDO1 的肿瘤也更可能具有最低四分位数的 CD8 浸润(每个高倍视野 <40， p = 0.024)。 结论。ASCC 具有多样化的免疫环境。尽管患者通常在标准治疗方面表现良好，但 IDO1 可作为预后不良的一个指标，可帮助确定可能受益于 IDO 靶向治疗的患者群体。 实践意义:在根治性放化疗后，患有局部晚期肛门癌的患者可能会有显著的治疗病损率和高复发风险。本研究的目的是确定肿瘤免疫微环境中的新型预后因素，以预测根治性放化疗的不良预后。本研究描述了局部肛门鳞状细胞癌 (ASCC) 治疗前的肿瘤免疫微环境，包括以前未在 ASCC 中研究过的两种标志物:吲哚胺 2,3 双加氧酶 1 (IDO1) 和 HLA I 类的特性。中位随访时间为 3 年，该研究表明，高 IDO1 表达与显著较低的 3 年总生存率相关(88% vs. 25%)。尽管最近对 IDO1 抑制剂的研究显示出的结果好坏不一，但本研究表明具有高 IDO1 表达的肛门癌患者具有并不乐观的预后并且可能代表了对靶向 IDO1 抑制发生反应的患者群体。 Despite increased incidence of anal squamous cell carcinoma (ASCC), treatment recommendations have remained unchanged for the past 35 years. This article profiles the tumor microenvironment of patients with localized ASCC, examining CD8, PD‐1, PD‐L1, IDO1 and HLA class I expression and, specifically, characterizes expression of IDO1 in the context of several key components of the immune microenvironment.